Speaking Anxiety and and English-Speaking Achievement: A Study Among Senior High School Students - Berlianti Mei Depi (Globish: An English-Indonesian Journal for English, Education, and Culture, 2026)
This study aims to determine the correlation between speaking anxiety and speaking achievement in English among eleventh-grade students at two high schools in Palembang. This study uses a quantitative correlational design. The sample consists of sixty-two students selected using convenience sampling. Data were collected through a speaking anxiety questionnaire and a speaking test assessed through an oral proficiency rubric. The results indicate that most students experience medium levels of anxiety, while their speaking achievement is in the enough to good category. The results of Pearson's correlation analysis show that there is no significant relationship between speaking anxiety and speaking achievement (r = 0.243; p = 0.057). These findings indicate that speaking anxiety is not the only factor that influences students' speaking achievement.